2019
DOI: 10.2196/preprints.13864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobile and Connected Health Technology Needs for Older Adults Aging in Place: Cross-Sectional Survey Study (Preprint)

Abstract: BACKGROUND An increasing number of mobile and wearable devices are available in the market. However, the extent to which these devices can be used to assist older adults to age in place remains unclear. OBJECTIVE This study aimed to assess older adults’ perceptions of using mobile and connected health technologies. METHODS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Interestedly, eventhough aging specific factors and elders' propensity related to technology has a negative relationship; there was a positive influence of aging specific factors on technology usage. This result further confirmed that positive attitudes of elders towards their own aging [45], self-image congruence, believing that using technology will facilitate to organizing in the life (Choudrie et al (2017) and more sensitive to ergonomic design of technology (regarding material, weight, comfort, quality and features) rather than price sensitivity [16] are leading elders to seriously consider using the specific technology. This result is further confirmed by negatively influence of aging specific factors on elders' technology resistance.…”
Section: Mediating Analysissupporting
confidence: 62%
See 1 more Smart Citation
“…Interestedly, eventhough aging specific factors and elders' propensity related to technology has a negative relationship; there was a positive influence of aging specific factors on technology usage. This result further confirmed that positive attitudes of elders towards their own aging [45], self-image congruence, believing that using technology will facilitate to organizing in the life (Choudrie et al (2017) and more sensitive to ergonomic design of technology (regarding material, weight, comfort, quality and features) rather than price sensitivity [16] are leading elders to seriously consider using the specific technology. This result is further confirmed by negatively influence of aging specific factors on elders' technology resistance.…”
Section: Mediating Analysissupporting
confidence: 62%
“…On the basis of considering attitudes of older adults towards their own aging could foster increased access to and usability of technologies to support their independent living [45]. We, therefore, propose to include five aging-specific factors namely; Self-image congruence (SIC); Aging Satisfaction (AS); Performance Expectancy (PE); Effort Expectancy (EE) and Functional Congruence (FC) to offer a more accurate indulgent of consumer acceptance or resistance of technology in the aspect of elderly community.…”
Section: Human-centric Factorsmentioning
confidence: 99%
“…User-centered design is an iterative process which focuses on understanding the user and their context, across each stage of the design process, including the user in the actual design process (Gardan, 2017). The reviewed literature identifies education as another effective tool in addressing some of the challenges and concerns pertaining to technology (Wang et al, 2016). Practitioners and researchers should work together to develop educational tools (i.e., technology classes, tech training), which can help enhance older adults' ability to utilize technologies across the continuum of embodiment.…”
Section: Design and Usability Of Embodied Technologiesmentioning
confidence: 99%
“…Smart technologies can also be customized to a degree to the unique needs and preferences of older adults [15,16] and are increasingly used to support occupational and leisure activities in various aspects of daily life [14,17]. To date, research has demonstrated that smart technologies can promote independent living, enhance health and well-being, and help to improve the quality of life in older adults and their caregivers [14,[18][19][20][21]. For example, smart wearable devices can serve as fall detection and prevention tools, providing alerts or notifications in case of a fall or sudden changes in movement patterns that can help older adults with their self-management and active engagement [22,23].…”
Section: Introductionmentioning
confidence: 99%